Thermalization dynamics of the quark condensate under strong magnetic fields - Frazon, Arthur Almeida [UNESP] (2024)
Strong magnetic fields affect quantum chromodynamics (QCD) properties in many situations, such as the early universe, magnetars, and heavy-ion collisions. A~QCD property affected by strong magnetic fields is the chiral quark condensate, an approximate order parameter of the QCD transition between a high-temperature quark-gluon phase and a low-temperature hadronic phase. In this dissertation, we studied numerically the thermalization dynamics of the quark condensate using a Langevin field equation derived by Krein and Miller in Symmetry 13, 551 (2021). The condensate is represented by the scalar-isoscalar field of the linear sigma model with quarks. Using the closed-time path formalism of nonequilibrium quantum field theory, the Langevin field equation is obtained by integrating out the quarks in a mean-field approximation. We solved numerically this equation within a quench scenario, in that the temperature of the system suddenly changes from a high temperature, at which the vaue of the condensate is very small, to low temperatures for which its value is nonzero. We showed that the solutions display an explosive initial growth and then damped oscillations toward an equilibrium value. The damping is determined by a dissipation coefficient that is due to the decay of the condensate into quark-antiquark pairs. The magnetic field has a dramatic effect on the dissipation coefficient, producing a considerably different thermalization scenario than thermalization in the absence of the field.